Kiss of the dragon - Besson, Luc; Nahon, Chris ([Beverly Hills, Ca.] : Hollywood Pictures Home Video, 2002)
While on a mission in Paris, China's top secret agent must team up with a call girl after he is falsely accused of murder
Editor, Marco Cave ; executive producer, Therry Arbogast
Cast: Jet Li, Bridget Fonda
VCD format
Keywords: Heroes in motion pictures; Violence in motion pictures